DIGITAL MARKETING TRAINING AND ASSISTANCE DURING PHYSICAL DISTANCING ON FARMERS GROUP IN MATANG ARA JAWA VILLAGE, MANYAK PAYED SUB-DISTRICT, ACEH TAMIANG REGENCY - Hanisah; Maria Hevianti; Murdhiani (LPPM dan PM Universitas Samudra, 2021)
The decision of physical distancing status by the central and regional governments in order to avoid the spread of covid-19 is considered to be able to disrupt food distribution. To conquer farmer’s income so that it does not decrease on the covid-19 pandemic, digital marketing technology is needed by utilizing social media that can help the farmers market their product directly to consumers. The community service carried out at the datok office in Matang Ara Jawa Datok, Banda Mulia sub-district, Aceh Tamiang Regency. The outcome of this service activities are (1) utilizing technology to increase farmers income, (2) utilizing Social media application (facebook, instagram, whatsapp, etc) so the marketing become broad, (3)Increasing farmers marketing by utilizing cell phones as means distributing agricultural product so that the selling price is higher, (4) (4) increasing awareness of the importance of technology in marketing agricultural products, especially during the Covid 19 pandemic, and (5) increasing the welfare of partners by relying on HP to get a higher income.